Pengaruh Pendidikan dan Pelatihan dalam mempersiapkan Sumber Daya Manusia pada dunia Aviation Maintenance Repair Organization di Indonesia - Frihatini, Farida; Arifin, Nanang; Efendie, Lukman; Qodariah, Qodariah (Universitas Pendidikan Indonesia (UPI), 2024)
Human resource management is a means to improve human quality, by improving human resources, increasing the performance and output power of the organization, so as to realize employees who have high performance so that a large role is also needed from the leadership of the organization. The purpose of this study was to determine the effect of education and training on the quality of human resources at the Maintenance Shop Unit of PT Batam Aero Technic. This research uses a quantitative approach. The sampling technique used was slovin and obtained a sampling of 50 employees. The data analysis technique used is multiple linear regression. The results of this study indicate that partially education has a positive effect on the quality of human resources. For training partially has a positive effect on the quality of human resources. And simultaneously education and training have a positive effect on the quality of human resources.